2007
DOI: 10.1093/nar/gkm114
|View full text |Cite
|
Sign up to set email alerts
|

R.KpnI, an HNH superfamily REase, exhibits differential discrimination at non-canonical sequences in the presence of Ca2+ and Mg2+

Abstract: KpnI REase recognizes palindromic sequence, GGTAC↓C, and forms complex in the absence of divalent metal ions, but requires the ions for DNA cleavage. Unlike most other REases, R.KpnI shows promiscuous DNA cleavage in the presence of Mg2+. Surprisingly, Ca2+ suppresses the Mg2+-mediated promiscuous activity and induces high fidelity cleavage. To further analyze these unique features of the enzyme, we have carried out DNA binding and kinetic analysis. The metal ions which exhibit disparate pattern of DNA cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 40 publications
2
35
1
Order By: Relevance
“…The enzyme exhibits promiscuous DNA cleavage characteristics in the presence of the natural cofactor Mg 2ϩ (143,144). Notably, the promiscuous activity is triggered by the binding of an additional metal ion to the enzyme (144).…”
Section: Promiscuity In Cofactor Utilization and Substrate Specificitymentioning
confidence: 99%
“…The enzyme exhibits promiscuous DNA cleavage characteristics in the presence of the natural cofactor Mg 2ϩ (143,144). Notably, the promiscuous activity is triggered by the binding of an additional metal ion to the enzyme (144).…”
Section: Promiscuity In Cofactor Utilization and Substrate Specificitymentioning
confidence: 99%
“…The REase exhibits remarkable versatility in substrate recognition and cofactor utilization, whereas the cognate MTase is very site-specific (14). In addition to its recognition sequence, GGTACC, the enzyme binds and cleaves a number of noncanonical sequences (i.e., TGTACC, GTTACC, GATACC, GGAACC, GGTCCC, GGTATC, GGTACG, GGTACT), with the binding affinity ranging from 8 to 35 nM (14,15). Accordingly, many of these sites are cleaved efficiently with k cat values varying from 0.06 to 0.15 min −1 vs. 4.3 min −1 for canonical sites (15).…”
mentioning
confidence: 99%
“…In addition to its recognition sequence, GGTACC, the enzyme binds and cleaves a number of noncanonical sequences (i.e., TGTACC, GTTACC, GATACC, GGAACC, GGTCCC, GGTATC, GGTACG, GGTACT), with the binding affinity ranging from 8 to 35 nM (14,15). Accordingly, many of these sites are cleaved efficiently with k cat values varying from 0.06 to 0.15 min −1 vs. 4.3 min −1 for canonical sites (15). The promiscuous activity of the enzyme is directed by a number of cofactors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The properties include prolific promiscuous activity in the presence of Mg 2ϩ which is further enhanced with Mn 2ϩ , efficient site specific high fidelity DNA cleavage when Ca 2ϩ is used instead of Mg 2ϩ , and suppression of the promiscuous cleavage activity in presence of Ca 2ϩ (21). Kinetic studies revealed that the Ca 2ϩ -mediated exquisite specificity is achieved at the step of DNA cleavage (22).…”
mentioning
confidence: 99%